2017
DOI: 10.1177/2399808317707967
|View full text |Cite
|
Sign up to set email alerts
|

A commuting spectrum analysis of the jobs–housing balance and self-containment of employment with mobile phone location big data

Abstract: Studies on the jobs–housing balance and self-containment of employment are mainly focused on observed journey-to-work trips using travel survey data. This study examines the relationship between the jobs–housing balance and the self-containment of employment through the use of mobile phone location data in Shenzhen, a megacity in southern China. Individual-level journey-to-work trips are explored based on mobile phone location big data. Self-containment of employment in the suburban districts is higher than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
(32 reference statements)
0
32
0
Order By: Relevance
“…Mobile phone location and activities aggregated for transportation use typically only include data when network connections are present and specific activities are recorded, described as a "potential activity bias" (Diao et al 2016, p. 938). Additionally, big data from mobile phone locations can obscure trips in which the origin and destination are within the same cellular tower range (Zhou et al 2018). However, big data sources may fill gaps in the needed information, as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mobile phone location and activities aggregated for transportation use typically only include data when network connections are present and specific activities are recorded, described as a "potential activity bias" (Diao et al 2016, p. 938). Additionally, big data from mobile phone locations can obscure trips in which the origin and destination are within the same cellular tower range (Zhou et al 2018). However, big data sources may fill gaps in the needed information, as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that these were highly consistent with the survey results. Zhou et al [38] analyzed the relationship between the job-housing balance and self-containment of employment using mobile phone data; their study revealed that self-sufficiency was higher in the suburbs than in the center, which meant that the job-housing balance policy had a positive effect on self-containment of employment in the suburbs; however, it had a limited effect in the central area. Zhang et al [39] also analyzed the job-housing balance using mobile phone data and found that the commuting pattern of Shanghai was far from the extremes and that the relative balance of jobs with respect to housing was decent.…”
Section: Research Of Big Datamentioning
confidence: 99%
“…Zhou et al [32] identified the residence and workplace of cellphone users from cellphone location data in Shenzhen. This study adopted a similar method, but with certain differences.…”
Section: Identifying Commuting Populationmentioning
confidence: 99%